Period effects in the risk of subsequent labour market marginalisation in young suicide attempters. (23rd September 2017) - Niederkrotenthaler, T; Helgesson, M; Rahman, S; Wang, M; Mittendorfer-Rutz, E
Abstract: Background: Suicide attempt in young age is associated with subsequent labour market marginalisation, but little is known about how marginalisation is affected by changes in suicide attempt rates and social insurance legislation and by age differences. Methods: Prospective cohort study based on register linkage of > 2.4 million Swedish residents per birth cohort, aged 19–40 years in 1999; 2004 and 2009, respectively, and followed up for 4 years. Suicide attempters treated in inpatient care in the three years preceding study entry ( n > 7000 per cohort) were compared with the general population of the same age without attempt (1987 to end of follow-up). Hazard ratios (HR) and 95% confidence intervals for long-term unemployment (>180 days), sickness absence (>90 days) and disability pension were calculated with Cox regression, adjusted for several risk markers. Additional analyses were stratified by age (below/above 30 years). Results: Across all cohorts, suicide attempt was associated with subsequent labour market marginalisation. Estimates were generally highest for disability pension [e.g. 2009 cohort: adjusted (a) HR = 2.7], followed by sickness absence (2009 cohort: aHR = 2.3) and unemployment (2009 cohort: aHR = 1.5). aHRs were higher in the 2004 and 2009 cohorts compared with the 1999 cohort. For disability pension, for example, aHRs were 2.39, 3.90 and 2.68 for the 1999, 2004 and 2009 cohorts, respectively. Stratification revealed marginal age differences. Conclusion: It seems to have become more difficult for suicide attempters to establish themselves on the labour market in later cohorts, which might result from changes in social insurance regulations. There were no considerable age differences.